Application of micro-calorimeter for metabolic monitoring - Tay, Karl Liquan (2014)
This paper aims to develop an experimental set-up of a micro-calorimeter for metabolic monitoring applications. Data acquisition software LabVIEW was explored and used to record the required data from our micro-calorimeter. The micro-calorimeter was functionalized with surface treatment procedures to mimic similar environments in the bone marrow where mesenchymal stem cells (MSCs) were extracted from, to prepare for cell attachment onto the surface of the micro-calorimeter reaction chamber. Preliminary data with MSC cells was collected and compared to data with water for comparison on sensitivity, stability. Potential uses of the micro-calorimeter for metabolic monitoring was researched in greater depth.